2021
DOI: 10.1111/soc4.12889
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of quantitative research on crime, the built environment, land use, and physical geography

Abstract: This paper provides a comprehensive review of space-and place-based criminology, with a focus on the relationship between crime, the built environment, land use, and/or physical geography, through sociological and critical geography lenses. An historical overview of major criminological and spatial theories and contributors is presented before examining the current state of the field. In honor of critical geography's goal to be "a people's geography," 1 this paper aims to be an accessible overview of space-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 116 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, the way this set of factors influences crime in the neighbourhood of train stations turned out to be largely different in another study (Liggett et al, 2001). A remarkable, complex review of current studies on the influence of the built environment, land use and environmental crime predictors on crime was made by A. R. Inlow (2021). She concluded that areas with lower crime rates are characterised by mixed-use areas and clear urban layout on a macro scale, while on a local scale the issues of lighting, building conditions, servicing and maintenance of green areas are of utmost importance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, the way this set of factors influences crime in the neighbourhood of train stations turned out to be largely different in another study (Liggett et al, 2001). A remarkable, complex review of current studies on the influence of the built environment, land use and environmental crime predictors on crime was made by A. R. Inlow (2021). She concluded that areas with lower crime rates are characterised by mixed-use areas and clear urban layout on a macro scale, while on a local scale the issues of lighting, building conditions, servicing and maintenance of green areas are of utmost importance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data contain a wealth of information on the spatial and temporal dynamics of crime and offer researchers the possibility to study the relationship between crime and demographics [40], housing, income, unemployment [41], education [42], economy [43], weather, climate [44], environment [45], social media [46], etc. For example, the literature studied the relationship between crime distribution and the land use data related to Szczecin, Poland [47].…”
Section: Temporal Crime Prediction Based On Crime and External Datamentioning
confidence: 99%
“…To improve the efficacy of preventing violent crime, this study used the police station border as the unit of analysis. This enables the police to focus more effectively on crime prevention analysis in small regions rather than vast areas, which is made possible by the deployment of smaller units [19] [20] and [21]. The issue of this study is the absence of comprehensive understanding indicates that, despite significant advancements in study that link between crime and the built environment, much still needs to be learned and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of this study is the absence of comprehensive understanding indicates that, despite significant advancements in study that link between crime and the built environment, much still needs to be learned and investigated. Further research is necessary because of the complicated nature of this link, which is influenced by several variables, including the city context, the type of crime, and socioeconomic situations [20]. The rationale for selecting Selangor, KLFT & PFT as the study area lies in their dense population, significant economic roles, diverse cultural landscape, well-developed infrastructure and urban planning, and the potential implications of research findings for policymaking.…”
Section: Introductionmentioning
confidence: 99%